Land Suitability and Capability For Mariculture Utilization of Coastal Area of Manado Tua Island - Adnan S. Wantasen; Wilmy. E. Pelle; Alex D. Kambey (Sam Ratulangi University, 2020)
The concept of land suitability and carrying capacity in utilizing the coastal land area of Manado Tua Island is a long-term goal in the study of sustainable coastal and small island management. Meanwhile, alternative livelihoods for sustainable aquaculture food sources are a special target. The potential of freshwater supply becomes a limiting factor for small islands, in addition to land availability. The special objective is the use of aquatic land as aquaculture land which has an impact on alternative livelihoods and the availability of food sources. The land suitability analysis is carried out in the following stages: (1) preparing a map of the Manado Tua Island area, (2) creating a matrix for the suitability of aquaculture activities, (3) providing weighting and scoring, and (4) conducting spatial analysis. The biogeophysical conditions of the coastal waters of Manado Tua Island are classified as normal for mariculture cultivation activities. Geographically the island is located at coordinates 01Âº 37 '57